Characterization of a-Si:H/c-Si Heterojunctions by Time Resolved Microwave Conductivity Technique - Amornrat Limmanee; Joaquim Nassar; Igor P. Sobkowicz; Jaran Sritharathikhun; Kobsak Sriprapha; Guillaume Courtois; Francois Moreau; Pere Roca I Cabarrocas (International Journal of Photoenergy)
In heterojunction solar cells, a-Si:H/c-Si heterointerface is of significant importance, since the heterointerface characteristics directly affect junction properties and thus solar cell efficiency. In this study, we have performed time resolved microwave conductivity (TRMC) measurements on n-type c-Si wafers passivated on both sides with intrinsic and doped a-Si:H layers in order to investigate electrical property and passivation quality of the a-Si:H/c-Si heterojunctions. It was found that the TRMC decay time and decay curve shape varied with the laser wavelength and power intensity and also depended on sample structures. By using 1064 nm laser pulse with high excitation, differences in the decay curve shape between samples with and without p-n junction were observed. The samples containing p-n junction(s) had unique slow decay mode, after the initial fast decay, which we ascribed to the release of carriers from the low-mobility amorphous layer into the high-mobility crystalline wafer as the built-in field of the junction was restored. Experimental results suggest that the TRMC is useful nondestructive technique which is suitable for primary check of the a-Si:H/c-Si heterojunctions during the solar cell fabrication process.